Zadania samorządu terytorialnego w zachowywaniu i upowszechnianiu dziedzictwa kulturowego. Doświadczenia powiatu nowosądeckiego - Węglarz, Stanisław (Studia Etnologiczne i Antropologiczne, 2014)
The implementation by the Nowosądeckie district of its statutory tasks in the area of culture through concrete action is dependent inter alia on geography, demographic situation, history and traditions, as well as on current social and cultural context. For this reason, the actual information on local government projects of Nowy Sącz district in the sphere of the protection and promotion of cultural heritage is preceded by a historical outline. This part deals with administrative divisions and basis of multiculturalism in the Nowy Sącz region. One of the most important tasks is to aid to preserve and promote the cultural heritage of the Nowy Sącz region in order to maintain the local identity.